Egyptian crude oil sorbent based on coated polyurethane foam waste - Mohamed Keshawy; Reem K. Farag; Amany Gaffer (Egyptian Journal of Petroleum)
In this study, free radical polymerization of hydrophobic monomer namely lauryl methacrylate & hexadecene is coated on the flexible polyurethane foam waste as an modifier of the non-polar moiety. Also various contents of magnetic nanoparticle are incorporated to the synthesized coated polyurethane foam waste. The coated sorbers are confirmed by X-ray photoelectron spectroscopy (XPS), scanning electron microscope (SEM) and thermogravimetric analysis (TGA). The coated polyurethane waste is used to absorb Egyptian crude oil to alleviate petroleum oil spill pollution. Moreover, Swelling and network parameters including maximum oil absorption (Qmax), swelling kinetics rates, polymer solvent interaction (χ), effective crosslink density (νe), equilibrium modulus of elasticity (GT), and average molecular weight among crosslinks (Mc) were decided and correlated to the efficiency of the synthesized coated waste. Keywords: Polyurethane foam waste, Coating, Oil spill, Networks parameters, Swelling parameters